Literasi Digital dan Implikasinya terhadap Kecakapan Berpikir Kritis Pegawai Pemerintah Dinas Perpustakaan dan Kearsipan Daerah Provinsi Sulawesi Utara - Rejune Junita Lesnussa (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
The urgency of digital literacy in the era of information disruption is related to the critical thinking skills of government employees, especially the Library and Archives Office of North Sulawesi Province. The development of information technology has been implemented, but it has not run optimally, due to the skills gab which is a crucial issue in accelerating digital transformation, knowledge is an obstacle. The obstacles include dimensions that have not been fulfilled in terms of digital skills, digital safety, digital ethics and digital culture. The research method used is qualitative with proposive sampling technique and data collection using observation, literature study and interviews. The results showed that digital literacy to use, understand and utilize digital technology, used as a measuring tool for the extent to which a person's competence and ability to adapt to current technological developments is not optimal and maximum, because human resources have not been able to implement digital literacy properly in carrying out work duties, lack of digital skills and knowledge, especially operating hardware devices and software devices. The utilization of digital tools with technology integration still uses a conventional system so that the implementation of work, fast and precise in terms of effectiveness, efficiency has not run optimally. Digital ethics is used by the government to be responsible for the data collected and clear consent, limiting the use of data for agreed purposes. Digital safety implementation is quite good, but there is a need for socialization to employees regarding the understanding of digital literacy and the importance of digital safety, especially malware or software. Need to understand the regulations and legal framework references used.